Implementation of The Internet of Things on Monitoring and Control Tools Hydroponic System - Ilham, Dirja Nur; Setiawan, Herry; Harahap, Muhammad Khoiruddin; Firnanda, Ary; Budiansyah, Arie (PERFECT: Journal of Smart Algorithms, 2024)
This Hydroponics is a way of growing crops without using soil. Soil that is actually a place for plants to grow can be supported with sand, husk charcoal and rockwool. In a hydroponic system, nutrients and the pH value of water are absolutely necessary for plant development, every plant that requires different levels of nutrients and pH values ​​of the air, if the nutrient levels are lacking then the plant will not grow as well as if the nutrient content is more then the plant will be poisoned. nutrients, water nutrients will continue to decrease along with the development of the plant itself. Therefore, a measuring tool for nutrient levels in hydroponic plant irrigation systems with android monitoring is made so that humans can monitor hydroponic plants. The tool used by Arduino nano as a microprocessor that is integrated into the TDS sensor works to measure nutrient levels and the pH sensor works to measure the pH value of the air, ESP8266 wifi module on NodeMCU as a gateway that aims to be a liaison from Arduino nano to the web server, Using websites and android applications that act as remote controls for nutrient pumps, pH up, pH down and hydroponic water pumps.